Electrochemical Reconstruction of NiFe/NiFeOOH Superparamagnetic Core/Catalytic Shell Heterostructure for Magnetic Heating Enhancement of Oxygen Evolution Reaction (Small 3/2023). Issue 3 (18th January 2023) - Peng, Dongquan; Hu, Ce; Luo, Xingfang; Huang, Jinli; Ding, Yan; Zhou, Wenda; Zhou, Hang; Yang, Yong; Yu, Ting; Lei, Wen; Yuan, Cailei
Abstract : Superparamagnetic Core/Catalytic Shell Heterostructures In article number 2205665, Cailei Yuan and co‐workers design and successfully prepare electrochemical‐reconstructed NiFe/NiFeOOH core/shell nanoparticles confined in highly conductive amorphous carbon matrix. Benefiting from the unique superparamagnetic NiFe/catalytic NiFeOOH core/shell heterostructure, their oxygen evolution reaction performance is improved significantly with an alternating magnetic field stimulation as the consequence of magnetic heating effect.